Does the Empirical Literature Inform Prevention of Dropout among Students with Emotional Disturbance? A Systematic Review and Call to Action. Issue 4 (1st October 2016) - Sullivan, Amanda L.; Sadeh, Shanna
ABSTRACT: For the past 30 years, the dropout rate for students with emotional disturbance has hovered around 50%, a rate substantially higher than the dropout rate for students with other disabilities and the general population. This systematic review evaluated the literature published between 1990 and 2013 on the effectiveness of dropout prevention and intervention for students with emotional disturbance. Only one experimental or quasi-experimental study tested a dropout prevention program with students with emotional disturbance meeting the methodological criteria for this review. The results reveal a dearth of research-based strategies or programs to support high school completion among students with emotional disturbance, underscoring the need for rigorous intervention research to improve outcomes for these students. We discuss implications for research and practice in light of this research gap.